Aesthetics of austerity in Toda Seiju's posters - Nguyen, Hung Ky (Monash University Publishing, 2013)
Japanese Post-modern posters emerged as a powerful medium that captivated the world’s attention in the 1980s. Their significance arises from their distinctive aesthetics, designers’ attempts to create their own styles, the environment where posters are displayed, and the social and cultural conditions that nurture the creativity of Japanese designers. Among the prominent Japanese designers in the Post-modern poster design field, Toda Seiju is notable for his austerity aesthetics. To find out more, I interviewed him in his Tokyo office on 30 October 2008. This paper sheds light on Toda’s aesthetics of subtraction, and how it informs his design practice. Through three case studies, I suggest that Zen philosophy and aesthetics have been incorporated to produce the intended effects in Toda’s work, with or without his awareness.